IMPROVING STUDENTS’ LISTENING COMPREHENSION IN REPORT TEXT BY USING DICTOGLOSS TECHNIQUE - Adhisty, Media Dyne; Sada, Clarry; ., Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This classroom action research was conducted in order to solve the problem that was encountered by the students in listening comprehension on report text. The research was implemented to 34 eleventh grade students of SMA Negeri 1 Pontianak. The tools of data collecting were observation checklist, field note, and test. The test was a statement evaluation. The students’ mean scores improved from 76.02 in the first cycle to 83.82 in the second cycle. The students achieved standard minimum score in the second cycle. Observation checklist and field note also showed improvement in teaching learning process. Pictures and important vocabularies activated students’ background knowledge about the topic and helped them to reconstruct the text. Working together with the deskmate encouraged the students to do their test.  They also became more active from cycle to cycle. It can be concluded that the students’ listening comprehension by using dictogloss technique was improved. Keywords: listening comprehension, dictogloss technique, report text   Abstrak: Penelitian tindakan kelas ini dilakukan untuk menyelesaikan masalah yang dihadapi oleh siswa dalam pemahaman mendengar pada teks laporan. Penelitian ini dilakukan terhadap siswa kelas XI SMA N 1 Pontianak yang berjumlah 34 siswa. Alat pengumpul data yang digunakan adalah tabel pemeriksaan, catatan lapangan, dan tes. Tes yang digunakan adalah evaluasi pernyataan. Skor rata-rata siswa meningkat dari 76.02 pada siklus pertama menjadi 83.82 pada siklus kedua. Itu berarti siswa dapat melewati standar ketuntasan pada siklus kedua. Tabel pemeriksaan dan catatan lapangan juga menunjukan peningkatan dalam proses belajar mengajar. Gambar dan kosakata yang disediakan mengaktifkan pengetahuan awal tentang topik dan membantu siswa membuat teks rekonstruksi. Bekerja sama dengan teman sebangku juga mendorong siswa untuk mengerjakan tes mereka. Mereka juga menjadi lebih aktif dari siklus ke siklus. Berdasarkan hasil tersebut, dapat disimpulkan bahwa pemahaman mendengar siswa meningkat melalui pengajaran menggunakan teknik dictogloss.   Kata Kunci: Pemahaman mendengar, teknik dictogloss, teks laporan